Digital fabrics for online shopping and fashion design - Haghzare, Leyla; Ping, Xiaona; Arnison, Matthew; Monaghan, David; Karlov, David; Honson, Vanessa; Kim, Juno (Frontiers in Virtual Reality, 2023)
Improving the digital presentation of fabrics enhances the online shopping experience and, in turn, reduces textile waste. In this study, we examined how the manipulation of simple surface reflectance models can bias the perception of fabric properties simulated online in a web browser. We showed that motion and three-dimensional (3D) folds (i.e., rumple) influence the perception of sheen for different fabric types (cotton knit and satin). Also, we found complex interactions between these parameters in their effects on perceived sheen and perceived color saturation. Moreover, we showed that changing the level of specular roughness significantly influences visual perception of sheen, color and lightness, which in turn, can categorically alter perceptual judgments of material type. In contrast to visual attributes, specular roughness did not influence visually perceived tactile characteristics of digital fabrics (thickness and stretch). The knowledge gained about perceptual biases of digital fabrics from this study will inform future considerations for optimizing the fidelity of textiles depicted in digital commerce.